Analysis of the Use of Online Learning Media by Teachers at SDN Ciputat Serang City in the Covid-19 Pandemic - Sekarini, Niken; Sutarjo, Ajo; Hanif, Muhammad (Universitas Pendidikan Indonesia Kampus Serang, 2021)
Online learning media is one of the learning and communication tools used by teachers and students during the Covid-19 pandemic. This study aims to determine the online learning media used by teachers, the learning process, mastery of learning media by teachers, and the use of learning media used by teachers at SDN Ciputat Serang City in online learning. The subject of this research is the teacher of SDN Ciputat Serang City in using online learning media. This research method is a case study. The approach in this research is qualitative. Data collection techniques used interviews and literature studies. The findings in this study indicate that the online learning media used by SDN Ciputat teachers are Whatsapp, Google meet, Zoom, Youtube, and Google classroom. The learning process is carried out online, the teacher sends materials and assignments through the online learning media used, the schedule and learning materials are adjusted to the current pandemic. Mastery of digital technology is not all teachers master the existing online learning media. The use of digital technology by teachers is related to student attitudes and responses as well as factors that support and hinder during the online learning process. Therefore, the solution used by teachers for the existing obstacles is to arrange teacher picket schedules at schools, home visits, and learning clinics.